'A woman's face and a child's body': Brooke Shields and child sexuality. Issue 2 (3rd April 2023) - Hatch, Kristen
ABSTRACT: In the 1970s, child actress and model Brooke Shields became a flashpoint for the crisis over child sexuality and paedophilia. Shields's disturbing marriage of a child's body with a womanly face disrupted the iconography of childhood that had flourished since the Enlightenment and pointed towards a new paradigm that has become more prominent in the decades since. This article examines how child liberationist views that children are sexual beings helped to shape Shields's public image as an object of adult male desire, even as her celebrity became a vector for the emerging feminist argument that children must be protected from adult desire. Through discourse about Shields, artists, journalists, and others articulated opposing logics for understanding the newly sexualised child and helped lay the foundation for contemporary debates about children in visual culture.